Photography in editorial design as a means of graphic communication. - Ramírez Chacón, Fernando (2017)
In editing images in editorial design, we refer to the location, printing and related aspects with a good editing and design of elements such as photographs, drawings, computer graphics, graphics and illustrations in the format to develop a graphic project. It is necessary to use these graphics in an editorial design and there should not be a gamble at your location and less design graphic image.The photograph must be designed before the photo shoot, in other words, the photographer should think and edit before placing your eye on the camera lens. It must be analyzed from its location to its function. A reference to this point is made because it is very usual to observe powers between text and images in graphic design; in other words, no editing.It is appropriate that photography communicates directly or complement way the note, so that the reader expands the information of what is being communicated. Use of this graphic resource is necessary to study and consider what is needed to communicate, and to determine how you are going to communicate the message? It is not “put” a photograph to fill a space in the format design, and level of composition. It is important to locate the element in a manner that complies with the appropriate space to have a good readability and relate directly to the other graphic design elements.For a designer to have a good photograph, it is necessary and important  to make necessary adjustments to appropriate it or graphic elements needed for editing and appropriate for reproduction technical conditions.Photography is an art, this is already proven, but designing a photograph with their texts in a format, it is even more, is going beyond the composition of a graphic element and form a compositional unity through their texts so they are a single element, where they do not compete with each other and achieve direct communication with the reader.It is convenient and necessary to adjust the pictures to the grid; it should be remembered that these elements interact with one another to be effective in graphic communication; this is where the grid achieves its goal of ordering the various elements and locate the place to each element in the composition and photography that it is not “set” or competing with other graphic elements.